2014
DOI: 10.1155/2014/507079
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Broadband Noise Sources of an Axial Fan under Rotating Stall Conditions

Abstract: Study on the influence of rotating stall on the aerodynamic noise of axial fan has important value to warn of the occurrence of stall through monitoring the noise variations. The present work is to analyze the aerodynamic noise before and after the phenomenon of rotating stall by solving Navier-Stokes equations, coupled with the throttle condition and the broadband noise sources model. The impeller exit rotational Mach number and rotational Reynolds number are separately 0.407 and 8.332 × 106 . The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, changes in these parameters are finally reflected with changes in integral parameters. Therefore, the verification method using integral parameters is widely applied in many researches [21,[24][25][26][27]. To verify the mesh independence, fans with mesh numbers of 3.82, 4.26, 4.65, 5.33 and 5.56 million are simulated in this study, as shown in Table 3.…”
Section: Meshingmentioning
confidence: 99%
“…However, changes in these parameters are finally reflected with changes in integral parameters. Therefore, the verification method using integral parameters is widely applied in many researches [21,[24][25][26][27]. To verify the mesh independence, fans with mesh numbers of 3.82, 4.26, 4.65, 5.33 and 5.56 million are simulated in this study, as shown in Table 3.…”
Section: Meshingmentioning
confidence: 99%
“…where k 0 is a constant, k 1 is throttle coefficient, ρ is density of the air, and U is velocity component of the z axial. Details of boundary conditions and throttle models are presented in [14].…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The internal flow field of the fan is related to the aerodynamic noise. The noises of the fan mainly consist of aerodynamic noise, machinery noise and radiation noise [14]. Among them, aerodynamic noise occupies the main position, which includes the rotational noise and vortex noise.…”
Section: Introductionmentioning
confidence: 99%
“…us, except for the unsteady flow of the pump when pump operates at partial load condition, the periodic instability caused by the internal rotor-stator interaction further deteriorates the flow field and operation condition. Even though the unsteady flow feature that results from partial load condition has been investigated deeply in the turbomachinery, compressor, and fan [23][24][25], there are few reports about the rotor-stator interaction or the shaft system vibration caused by the rotor-stator interaction of the mixed-flow pump under the circumstance of partial load condition, and the relationship between the shaft vibration and rotor-stator interaction flow is also not revealed. Many scholars just focus on the hydrodynamic instabilities caused by unsteady characteristic of rotor-stator interaction flow or the energy loss of the pump running at partial load condition.…”
Section: Introductionmentioning
confidence: 99%